Redescription of Congrhynchus talabonoides Fowler, 1934 (Anguilliformes: Congridae) based on specimens collected from the Philippines, Taiwan and India - Smith, David G.; Ho, Hsuan-Ching; Sumod, K. S. (Zootaxa, 2018)
The rare congrid eel species Congrhynchus talabonoides Fowler, 1934 was described from three specimens collected in the Philippines during the Albatross expedition in 1908–1909. The only mention of the species in the literature since its description has been in a type catalog (Smith, 1994), an identification guide (Smith, 1999), and a checklist of the eels of Taiwan (Ho et al., 2015, where it was erroneously placed in the Muraenesocidae). The first author discovered the Taiwan specimen in 2009 during a visit to the National Museum of Marine Biology and Aquarium in Taiwan, the first new specimen reported since its description more than 100 years ago. Several specimens were recently collected in the Andaman Sea. Based on these new specimens and a re-examination of the original three type specimens, we provide a full redescription of the species below.